Changes in photosynthesis with increasing salinity in mangrove ecosystem - R. Ranganathan; A. K. Rajalakshmi; P. Elavazhahan; P. Manivannan (Innovations in Agriculture, 2019)
The present study was carried out in Lumnitzera racemosa Willd. a dicotyledonous mangrove (family: Combretaceae). NaCl at the rate of 0 (control), 100, 200, 300, 400, 500, 600, 700, 800, 900 and 1000 mM were given to 1 month old and fully established seedlings. Samplings were done on 60th 120th and 180th days after NaCl treatment. Chlorophyll, carotenoids, Net leaf photosynthesis, photosynthetic carboxylases and amylases were estimated from the samples. Salinity from sodium chloride encouraged the synthesis of carotenoid and chlorophyll in L. racemosa to the ideal concentration. When NaCl salinity is increased, photosynthetic properties such net leaf photosynthesis, stomatal conductance, transpiration, leaf chamber temperature, and intercellular CO2 concentration decreased. This information can be used to assess the effect of increasing concentration of salinity in crop plants.